D–A–D-type narrow-bandgap small-molecule photovoltaic donors: pre-synthesis virtual screening using density functional theory. Issue 22 (19th May 2016) - Gim, Yeongrok; Kim, Daekyeom; Kyeong, Minkyu; Byun, Seunghwan; Park, Yuri; Kwon, Sooncheol; Kim, Heejoo; Hong, Sukwon; Lansac, Yves; Jang, Yun Hee
Abstract : A new series of D–A–D-type small-molecule photovoltaic donors are designed and screened before synthesis using time-dependent density functional theory calculations. Abstract : A new series of D–A–D-type small-molecule photovoltaic donors are designed and virtually screened before synthesis using time-dependent density functional theory calculations carefully validated against various polymeric and molecular donors. In this series of new design, benzodithiophene is kept as D to achieve the optimum highest-occupied molecular orbital energy level, while thienopyrroledione is initially chosen as A but later replaced by difluorinated benzodiathiazole or its selenide derivative to achieve the optimum band gap. The D–A–D core is end-capped by pyridone units which could not only enhance their self-assembly via hydrogen bonds but also play a role as an acceptor (A′) to form an extended A′–D–A–D–A′ small-molecule donor.